Systematic Review Kapasitas Sumber Daya Aparatur Desa Dalam Pengelolaan Dana Desa - AS, MN Romi; Nanarhati S, Emei Dwi; Ikhwaningrum, Dian Utami; Dwi Rahmawati, Desy Ayu Nining; Firmansyah, Jhonny Indrianto (REFORMASI, 2024)
The main objective of this systematic review article is to examine the capacity of human resources. The author addresses the research question regarding the capacity of village government human resources in managing village funds. The author first outlines the scholarly perspectives (Village Apparatus Capacity and Village Fund Management); indicators of successful village fund management (Accountability in village fund management and Innovations in village fund management); and the Implications of Enhancing the Capacity of Village Apparatus in Village Fund Management (Improved knowledge and compliance in village fund management as well as increased benefits experienced by village communities).Tujuan utama dari artikel systematic review ini ialah untuk mengetahui Kapasitas Sumber Daya Manusia. Penulis menjawab pertanyaan riset tentang Bagaimana Kapasitas Sumber Daya Manusia Pemerintah Desa dalam pengelolaan dana desa. Penulis mengambarkan dulu pandangan keilmuan (Kapasitas Aparatur Desa danPengelolaan Dana); indikator keberhasilan pengelolaan dana desa (Akuntabilitas pengelolaan dana desa dan Inovasi pengelolaan dana desa); dan Implikasi Peningkatan Kapasitas Aparatur Desa Dalam Pengelolaan Dana Desa (Peningkatan pengetahuan dan kepatuhan dalam pengelolaan dana desa serta Peningkatan manfaat yang dirasakan masyarakat desa).